Strategi Peningkatan Keselamatan Transportasi Jalan - Eko Agus Susanto; Eleonora Sofilda; diyono bambang ledoh (Department of Civil Engineering, Diponegoro University, 2025)
The increasing number of road traffic accidents and the high fatality rate in Indonesia, encourage the Government to develop strategies and preventive measures to reduce accidents in the short, medium and long term, although until now the fatality rate is still high. The purpose of this study is to analyze the influence of regulatory factors, humans, traffic signs, supervision and enforcement, and vehicles with technological variables as intervening factors on road safety in an effort to reduce the level of traffic accidents in Indonesia. The location of the study was conducted in 34 provinces in Indonesia, using quantitative data analysis through questionnaires on 500 respondents, with the SEM method (Smart Pls 4.0). The results of the study explain that regulatory factors, humans, traffic signs, supervision and enforcement, and vehicles with technological variables have a positive and significant influence on traffic safety, which means that an increase in the performance of the independent variables has a positive impact on traffic safety. The recommendations from this study are the priority of traffic safety improvement policies, namely: increasing active and passive safety in vehicles, using safety technology in vehicles, utilizing CCTV and e-ticketing for supervision and enforcement, fulfilling ffective and efficient traffic signs and safety campaigns for road users and improving regulations.